Catalytic Conversion of CO2 into Alcohols: Comparison of Supports - Zulkifli, N.I. (Springer Science and Business Media B.V., 2021)
Promoted Bimetallic Cu/ZnO catalysts were synthesized on Al2O3, Al2O3-ZrO2 and zeolite supports. The catalytic performances in CO2 hydrogenation reaction were evaluated in a fixed-bed reactor system at H2:CO2 (3:1), 22.5Â bar and 250Â Â°C for 5Â h. The catalyst supported on Al2O3âZrO2 resulted in the highest CO2 conversion (15.81) and methanol selectivity (68.77). In general, all the tested catalysts show low selectivity towards ethanol. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.